2018
DOI: 10.3390/jfmk3040060
|View full text |Cite
|
Sign up to set email alerts
|

Lactate, Heart Rate and Rating of Perceived Exertion Responses to Shorter and Longer Duration CrossFit® Training Sessions

Abstract: The aim of this study was to analyze blood lactate concentration (LAC), heart rate (HR), and rating perceived exertion (RPE) during and after shorter and longer duration CrossFit® sessions. Nine men (27.7 ± 3.2 years; 11.3 ± 4.6% body fat percentage and training experience: 41.1 ± 19.6 months) randomly performed two CrossFit® sessions (shorter: ~4 min and longer: 17 min) with a 7-day interval between them. The response of LAC and HR were measured pre, during, immediately after, and 10, 20, and 30 min after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 19 publications
1
36
0
3
Order By: Relevance
“…The training intensity was verified in a few studies through heart rate (HR) assessment, in which the HR remained between 85.9 and 97.4% of the maximum HR (Fernandez-Fernandez et al, 2015 ; Murawska-Cialowicz et al, 2015 ; Kliszczewicz et al, 2018a , b ; Maté-Muñoz et al, 2018 ; Tibana et al, 2018 ; Ahmad et al, 2019 ; Feito et al, 2019a ). Regarding the WOD time, 10 studies used protocols with times <10 min (Fernandez-Fernandez et al, 2015 ; Kliszczewicz et al, 2017 , 2018a , b ; Maté-Muñoz et al, 2017 , 2018 ; Mangine et al, 2018 , 2019 ; Tibana et al, 2018 ; Timón et al, 2019 ), 13 studies used protocols with times between 10 and 19 min (Murawska-Cialowicz et al, 2015 ; Shaw et al, 2015 ; Escobar et al, 2016 , 2017 ; Kliszczewicz et al, 2017 , 2018a , b ; Maté-Muñoz et al, 2017 ; Durkalec-Michalski et al, 2018 ; Mangine et al, 2018 , 2019 ; Tibana et al, 2018 ; Feito et al, 2019a ), and five studies used protocols with times over 20 min (Fernandez-Fernandez et al, 2015 ; Maté-Muñoz et al, 2017 , 2018 ; Mangine et al, 2018 ; Tibana et al, 2019b ).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…The training intensity was verified in a few studies through heart rate (HR) assessment, in which the HR remained between 85.9 and 97.4% of the maximum HR (Fernandez-Fernandez et al, 2015 ; Murawska-Cialowicz et al, 2015 ; Kliszczewicz et al, 2018a , b ; Maté-Muñoz et al, 2018 ; Tibana et al, 2018 ; Ahmad et al, 2019 ; Feito et al, 2019a ). Regarding the WOD time, 10 studies used protocols with times <10 min (Fernandez-Fernandez et al, 2015 ; Kliszczewicz et al, 2017 , 2018a , b ; Maté-Muñoz et al, 2017 , 2018 ; Mangine et al, 2018 , 2019 ; Tibana et al, 2018 ; Timón et al, 2019 ), 13 studies used protocols with times between 10 and 19 min (Murawska-Cialowicz et al, 2015 ; Shaw et al, 2015 ; Escobar et al, 2016 , 2017 ; Kliszczewicz et al, 2017 , 2018a , b ; Maté-Muñoz et al, 2017 ; Durkalec-Michalski et al, 2018 ; Mangine et al, 2018 , 2019 ; Tibana et al, 2018 ; Feito et al, 2019a ), and five studies used protocols with times over 20 min (Fernandez-Fernandez et al, 2015 ; Maté-Muñoz et al, 2017 , 2018 ; Mangine et al, 2018 ; Tibana et al, 2019b ).…”
Section: Resultsmentioning
confidence: 96%
“…This increase seems to occur at the beginning of the training and persists for up to 30 min after the session (Tibana et al, 2018 ). Some studies presented differences between the different WODs (Tibana et al, 2016 ; Maté-Muñoz et al, 2017 , 2018 ; Timón et al, 2019 ), and some found no differences (Fernandez-Fernandez et al, 2015 ; Durkalec-Michalski et al, 2018 ; Tibana et al, 2018 , 2019b ). Chronically, Murawska-Cialowicz et al ( 2015 ) reported non-significant changes in lactate values after 3 months of CrossFit ® training.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations